2015
DOI: 10.1007/978-3-319-25897-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Enterprise Architecture Management – Insights from European Experts

Abstract: Part 6: Investigating Enterprise ModelsInternational audienceExcellence in IT is a key enabler for the digital transformation of enterprises. To realize the vision of Digital Enterprises it is necessary to cope with changing business requirements and to align business and IT. In order to evaluate the contribution of Enterprise Architecture Management to these goals, our paper explores the impact of various factors to the perceived benefit of EAM in enterprises. Based on literature, we build an empirical resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that there are various important impact factors that influence the benefits of EAM [8], [13]- [16]. Such studies as [17], [18] have examined how EAM can contribute to strategic change processes or support the achievement of corporate goals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that there are various important impact factors that influence the benefits of EAM [8], [13]- [16]. Such studies as [17], [18] have examined how EAM can contribute to strategic change processes or support the achievement of corporate goals.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the acceptance of business has massively increased, as mentioned before, and the education offerings, one of the postulations in the study, can cover the requirements. Schmidt et al [15] presented in 2015 the empirical research "Benefits of Enterprise Architecture Management -Insights from European Experts" summarizing the answers of 263 IT experts from central Europe about the impact of several aspects on the benefit of EAM in enterprises. They showed that "changing business requirements, IT Business Alignment, the complexity of Information Technology infrastructure as well as enterprise architecture knowledge of Information Technology employees are crucial impact factors to the perceived benefit of EAM in enterprises".…”
Section: Related Workmentioning
confidence: 99%
“…Unlike traditional network embedded systems, the IoT connects different devices from various manufacturers for a variety of purposes (Kovatsch et al., 2012). This revolution based on CPS is integrating heterogeneous data and knowledge (Lu, 2017), merging the digital and the physical workflow (Schmidt et al., 2015).…”
Section: Industry 40 and National Programmesmentioning
confidence: 99%
“…CPS can be defined as engineered systems that include interacting physical and computational components (Manyika et al, 2013). CPSs, by connecting the real and the virtual world (Schmidt et al., 2015), are determining new ways of creating and offering value through ecosystems that go beyond individual value chains (Ibarra et al., 2018).…”
Section: Introductionmentioning
confidence: 99%